1960
DOI: 10.1002/j.1551-8833.1960.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Modified Method for Colorimetric Determination of Selenium in Natural Water

Abstract: This paper begins by providing a brief overview of the development of methods for the determination of selenium. Results of a study by Cheng in 1956 found that at a pH greater than 5, piazselenol could be quantitatively extracted with toluene, benzene, or xylene, butyl, and amyl alcohols and that ethylenediaminetetraacetic acid tetrasodium salt (EDTA) can be used to minimize the interference of polyvalent metals. The objective of the study described in detail in this paper was concerned essentially with reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…of aqueous phase and 5 ml. of toluene indicated that a recovery of 74 ±2% would be obtained with one extraction; there is no advantage (14) in attempting to increase the per cent extracted by increasing the number of extractions, because the volume of the organic phase will also be increased.…”
Section: Recovery Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…of aqueous phase and 5 ml. of toluene indicated that a recovery of 74 ±2% would be obtained with one extraction; there is no advantage (14) in attempting to increase the per cent extracted by increasing the number of extractions, because the volume of the organic phase will also be increased.…”
Section: Recovery Experimentsmentioning
confidence: 99%
“…Handley and Johnson (7) have used the same reaction with plant material and report that 0.25 Mg. of Se may probably be determined with confidence. Magín et al (14) use this method for measuring Se in water.…”
mentioning
confidence: 99%
“…The water samples were analyzed by the U.S. Geological Survey laboratory in Worland, Wyo., using the method described by Magin, Thatcher, Rettig, and Levine (1960). The accuracy of the determination is somewhat sensitive to interference from other minerals at high concentrations of total dissolved solids.…”
Section: Methods Of Investigationmentioning
confidence: 99%